KAJIAN GEOLOGI LINGKUNGAN PADA LOKASI PENAMBANGAN BATUAN DIABAS GUNUNG PARANG DALAM RANGKA KONSERVASI BATUAN DI CAGAR ALAM GEOLOGI KARANGSAMBUNG - Mustofa Nur, Arief (Diponegoro University, 2011)
Diabas Parang hill is one of location which conservated in area conservation of geological Karangsambung.Now, it is threatened, because there are many mines at surrounding it. Activities of mining not care science andenvironmental conservation.Impact of mining so cause change of topography/morphology, slope become more steep, and mining locationbecome potentially accure rock fall and landslide. Pursuant to result of laboratory analysis, engineeringproperties diabas Parang hill strongless than andesit so it is only fulfil for trotoir.For diabas conservation which is protected so need affort to stop activity of mining. The effort can do seekingaltenative location for mine and/or to change mine activities.